Implementing sustainable mission command in the Hellenic Army. Issue 1 (2nd January 2018) - Ploumis, Michail; Pilalis, Labros E.
Abstract: The modern Mission Command philosophy in military operations originated with the German concept of Auftragstaktik (mission tactics). It emphasizes in general terms the exercise of disciplined initiatives by subordinates during the execution of mission-type orders in the course of military operations that are conducted within the overall intent of a commander. The present paper contains an overview of the historical evolution of the mission command concept and its application. The paper compares the mission command concept with the detailed or linear method of command. This paper focuses on the relevance of the mission command concept for the Hellenic Land Forces (HLF) in Greece. The paper provides a historical account on when and where mission command was successfully exercised by the Hellenic Armed Forces in the modern military history of Greece. The authors support the premise that the mission command concept is essential for safeguarding Greek national security in the current environment of evolving symmetric and asymmetric threats, and in meeting operational challenges in a diverse and difficult terrain. The paper examines the cultural reasons that have impeded the adoption of the mission command concept within the HLF and recommends a three-phase model for its permanent implementation.